Variasi Genetik dalam Populasi Kultivar Kopi Arabika Berbuah Kuning di Lahan Petani Berdasarkan Penanda SSRs - Randriani, Enny; Dani, Dani; Izzah, Nur Kholilatul (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Identification of the genetic diversity within populations of yellow-berried Arabica coffee cultivar based on morphological characters faced an obstacle in finding identical environmental conditions at farmers field. Therefore, an approach which is not influenced by differences in environmental conditions is required, for instance based on DNA polymorphism. The research aimed to analyze genetic variation within populations of yellow-berried Arabica coffee cultivar based on SSRs markers. The research was conducted in the Integrated Laboratory, Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, from April until June 2015. The leaf samples for DNA extraction were obtained from yellow-berried Arabica coffee cultivar (AGK-1) and two red-berried cultivars as controls, namely ABP-1 (dwarf type) and Typica (tall type). AGK-1 and ABP-1 cultivars consisted of 17 and 5 individual numbers, respectively, whereas Typica cultivar comprised three individuals. PCR amplification was carried out using 12 SSR primers. Four primers (M24, SSRCa052, M32, and M42) produced polymorphic band. The binary data obtained in this research was subsequently processed using NTSYS-PC program version 2.1. The genotypes were grouped based on a genetic similarity matrix using the unweighted pair group method arithmetic mean (UPGMA). The result showed the existence of genetic variation among individual of AGK-1 cultivars, which forming three clusters at the genetic similarity value of 67%. One cluster exhibited close genetic relationships between some individuals within the population of AGK-1 cultivar and Typica cultivar. Meanwhile, the other two clusters showed high genetic similarity between AGK-1 cultivar and ABP-1 cultivar. The result demonstrated the possibility of gene flow between genotypes or residual heterozygosity within the population of AGK-1 cultivar at farmers field, which required a further study.